0146 Exposure to respirable welding fume and iron status in German welders. (23rd June 2014) - Casjens, Swaantje; Henry, Jana; Lehnert, Martin; Weiss, Tobias; Kendzia, Benjamin; Lotz, Anne; Van Gelder, Rainer; Berges, Markus; Hahn, Jens-Uwe; Brüning, Thomas; Pesch, Beate
Abstract : Objectives: Siderosis due to excessive iron exposure is a rare disease in welders. Less is known about the effect of inhaled iron on systemic iron status in welders. Here we present the association between exposure to iron as major constituent of the welding fume and the iron status in German welders. Method: In this analysis we included 192 welders from the German WELDOX study not wearing respirators. Respirable welding fume was measured during one shift and analysed for its metal content. Iron status was assessed with different measures, including serum iron, serum ferritin (SF), transferrin, and prohepcidin. High iron stores were classified according to international standards. The influence of exposure to iron and other factors on the iron status was analysed with multiple regression models. Results: Median shift exposure to respirable iron was 88 µg/m³ (interquartile range 13–690 µg/m³). For the overall study population the prevalence of high iron stores (SF > 200 µg/L) was 31.3%. A lower prevalence was found for tungsten inert gas (TIG) welders (16.9%). For all other welders using welding techniques with higher emission rates it was 38.6%. The regression models revealed a significant association of respirable iron and prohepcidin (exp (β)=1.08, 95% CI 1.05; 1.11) and a weaker association between respirable iron and serum ferritin (exp (β)=1.06, 95% CI 1.00; 1.12). Conclusions: Although the iron status is biologically well regulated we found positive associations of respirable iron in welding fumes on prohepcidin and ferritin. We observed more welders with high iron stores in comparison to male persons from the general population.